Sport Organizations Leadership, Governance and Its Challenges: Systematic Review: Leadership, Governance and Its Challenges - Admit, Daniel Getnet (Indonesian Journal of Sport Management, 2024)
The objective of this systematic review was to compressively review sports organizations leadership, governance, and challenges by synthesizing the current literature. Systematic review is used through the PRISMA protocol; we conducted a search from the Google Scholar data base. From the initial 540 studies reviewed, 75 studies were used for this study that met the inclusion criteria. The findings are inconclusive, and unidirectional. However, geographical, commercial, digital, and social globalisation dominates the theoretical positions in the current literature. On the other hand, a global outlook with fidelity to local roots, changing commercial partnerships, a changing media landscape, cultural battles, and the attractiveness are five patterns identified in the sport organization. Now a day principles, gender issue, technology, human right, structure etc. faces unique challenge in sport organizations leadership and governance. Therefore, practitioners, academicians, or scholars can make a deep review and investigation in this issue.